Healthcare provision for displaced people in transit: Analyses of routinely collected data from INTERSOS clinics at the Ukrainian border with Moldova and Poland - Saleh Aljadeeah; Seyed-Moeen Hosseinalipour; Nataliia Khanyk; Eszter Szocs; Aliki Traianou; Ana Tomas; Chrysanthi Tatsi; Elżbieta Czapka; Alessandro Verona; Tessa van Boekholt; Ion Chesov; Apostolos Veizis (Journal of Migration and Health)
Background: The Russian military invasion of Ukraine has sparked Europe's largest forced displacement since World War II, bringing about significant health vulnerabilities for migrants and refugees. European health information systems lack comprehensive data coverage, especially in underrepresented migration stages like transit. This study aims to address this gap by analyzing data from INTERSOS clinics at the Moldovan and Polish borders with Ukraine to identify the common health conditions prompting people to seek healthcare services during transit. Methods: From 6th March to 31st May 2022, this cross-sectional study observed migrants and refugees receiving INTERSOS services at two mobile clinics in Moldova, and a facility in Poland. We analyzed data by age, sex, nationality, and reported disease frequencies and care provided. Results: This study used routinely collected data from 1756 patients. The majority of the adult population seeking healthcare were females (76.5 %), 26.1 % were children and 18.7 % were older individuals. Noncommunicable diseases (NCDs) were the primary reason for seeking healthcare at these clinics, with 23.3 % of the study population being diagnosed with at least one chronic disease, and 3.4 % of people having multimorbidity. Mental and behavioural disorders were diagnosed in 12.6 % of the population, and somatoform disorders and related stress (F40-F48) in 10.8 %. Discussion: Our study indicates the diversity of forcibly displaced populations and the corresponding diversity of their healthcare needs. In the shadow of a forced displacement crises triggered by the conflict in Ukraine, there is an urgent need to give more attention to subgroups of the population that are often neglected in humanitarian crises. These include older adults, females, and ethnic minorities. Additional attention should also be given to NCDs and sexual and reproductive health (SRH) care needs, especially given the high numbers of older adults and females in this population. Early medical support, psychological first aid and interventions in transit centers that promote survivor resilience and recovery are required. Conclusion: Our findings shed light on the healthcare needs of forcibly displaced populations during transit, a stage often overlooked in migration health research. They underscore the diverse healthcare needs of forcibly displaced populations, emphasizing the necessity for humanitarian aid programs to acknowledge and address this diversity. Accessing data on displaced populations' healthcare needs in transit can help the preparing and planning of healthcare services for these populations in host or destination countries. Ensuring objective anonymization and preventing patient re-identification are essential, particularly in safeguarding refugee privacy and data protection to avoid the misuse of their data.